Ecological factors affecting first-time mothers' satisfaction with Sanhujoriwons (postpartum care centres) from South Korea: a cross-sectional and correlational study - Ju-Eun Song; Soyeon Lee; Min Kyong Lee; Hyun-Ju Chae (BMC, 2023)
Abstract Background In South Korea, commercial postpartum care centres, known as Sanhujoriwons, have emerged as important institutions aiding mothers' physical recovery after childbirth. Although previous studies have measured mothers' satisfaction level with Sanhujoriwons, this study applies Bronfenbrenner's ecological model to identify the factors influencing first-time mothers' satisfaction with Sanhujoriwons. Methods This descriptive correlational study involved 212 first-time mothers admitted to Sanhujoriwons for two weeks with their new-borns (healthy babies weighing at least 2.5 kg) after giving birth after 37 weeks of pregnancy. Data were collected using a self-report questionnaire at five postpartum care centres in the metropolitan area of South Korea from October to December 2021, on the day of the mothers' discharge. This study considered ecological factors such as perceived health status, postpartum depression, childcare stress, maternal identity at the individual level; partnership with Sanhujoriwon staff at the microsystem level; and the Sanhujoriwons' education support system at the exo-system level. The data were analysed using descriptive statistics, t-test, one-way ANOVA, correlation analysis, and hierarchical regression analysis using the SPSS 25.0 Win program. Results The mean score of satisfaction with Sanhujoriwons was 59.67 ± 10.14 out of 70, indicating a high level of satisfaction. The hierarchical regression analysis showed that satisfaction with Sanhujoriwons was significantly affected by the perceived health status (β = 0.19, p < 0.001), partnership between mothers and the caregivers (β = 0.26, p < 0.001), and education support system of the Sanhujoriwons (β = 0.47, p < 0.001). The explanatory power of the model for these variables was 62.3%. Conclusions Our results indicate that not only the mother's health status but also the educational support system of postpartum care centres and partnerships are important for improving first-time mothers' satisfaction with postpartum care centres. Thus, when developing an intervention program for postpartum care centres, practitioners should focus on developing various kinds of support and strategies to improve the physical health condition of mothers, build partnerships between mothers and care staff, and improve the quality of the educational support offered to mothers. Further studies to develop and test the effectiveness of such intervention programs are strongly suggested.